Gujarat To Malacca: Trade Routes and the Process of Islamization in the Malay Archipelago - Ayu Annur Fani; Nyayu Soraya; Baldi Anggara (FKIP - Universitas Riau, 2026)
This study presents an analysis of Malay civilization and its pivotal role in history, emphasizing that Islamization occurred through longterm social, economic, and cultural interactions. It aims to explain the strategic role of trade routes between Gujarat and Malacca in spreading Islam across the Malay Archipelago. Using a qualitative library research method, the results show that Gujarat functioned as a major trade center and primary intermediary in the Indian Ocean since the 13th century. Through maritime activities, Muslim traders introduced Islamic teachings to Malacca, which evolved into the archipelago’s main religious center. Beyond economic factors, this process was strengthened by intermarriage, cohesive Muslim communities, and adaptive da'wah. Furthermore, the role of Islamic scholars (ulama) was crucial as they served as religious teachers, political advisors, and intellectual figures who adapted Islamic teachings into local Malay culture. This research underscores that such cultural adaptation laid the groundwork for a moderate form of Islam in the archipelago. Ultimately, these historical dynamics provide vital insights into the resilient and adaptive nature of Islamic civilization in Southeast Asia.